2005
DOI: 10.1080/00016470510030346
|View full text |Cite
|
Sign up to set email alerts
|

Periacetabular osteotomy

Abstract: Background When surgical treatment of dysplastic hip osteoarthrosis is necessary, osteotomy is preferable to fusion or THR. We evaluated periacetabular osteotomy as a method of choice.Patients and methods We treated 36 symptomatic dysplastic hip joints (32 patients) with the Bernese periacetabular osteotomy (PAO) between 1994 and 2001. We used the ilio-inguinal (I-I) approach in 32 hips and a modified Smith-Petersen (S-P) approach in 4. The patients were followed for mean 4 (1.5-8) years. In 1 patient with cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The issue of VTE after pelvic and/or femoral osteotomy has been evaluated previously. The incidence of VTE in patients undergoing PAO has been reported to be very low at 0% to 5% [541][542][543][544][545][546] . Although the incidence of VTE after osteotomy seems to be lower than that after total joint arthroplasty without prophylaxis, these values are not negligible and VTE prophylaxis should still be considered.…”
Section: Arielmentioning
confidence: 99%
“…The issue of VTE after pelvic and/or femoral osteotomy has been evaluated previously. The incidence of VTE in patients undergoing PAO has been reported to be very low at 0% to 5% [541][542][543][544][545][546] . Although the incidence of VTE after osteotomy seems to be lower than that after total joint arthroplasty without prophylaxis, these values are not negligible and VTE prophylaxis should still be considered.…”
Section: Arielmentioning
confidence: 99%
“…Van BerGayk et al included 22 patients, reporting significant improvement in pain and function 24 months after PAO within both the WOMAC and the SF-36 scores, although not in the SF-36 mental component score[ 12 ]. Several studies with a retrospective design all showed a significant drop in pain and an increase in the activity component of their patient-reported outcomes [ 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructive osteotomies aim to restore normal hip anatomy and are subdivided into three groups: acetabuloplasty with distal mobilization of the acetabular roof (Pemberton, Albee-Lance, Dega, San Diego), redirectional osteotomies involving the displacement of pelvic fragments (Salter, Le Coeur, Hopf, Steel, Sutherland-Greenfield, Kalamchi, Tönnis-Trousseau, PemberSal), and pelvic osteotomies with the reorientation of the acetabulum (Blavier, Wagner, Eppright, Ninomiya, Hsieh, Ganz-Bernese). Salvage osteotomies, recommended post-bone maturity, aim to postpone arthroplasty and provide enhanced coverage of the acetabular component during arthroplasty (Chiari, Wilson, Staheli) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%